2017
DOI: 10.1016/j.vaccine.2017.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Waning protection of influenza vaccination during four influenza seasons, 2011/2012 to 2014/2015

Abstract: Waning of vaccine protection was observed among individuals aged 65years old or over in two A(H3N2)-dominant influenza seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Our estimate was lower than those reported from the United States (61%, 95% CI: 52%, 68%) [19] and Canada (58.5%, 95% CI: 43.9%, 69.3%) [20], which could attribute to different circulating viruses in the two regions. In the 2013- 14 for the elderly aged 65 years or above [20] while a similar study in Spain estimated a 248 moderate influenza VE of 33% (6%, 53%) and 40% (13%, 59%) in all age groups and the elderly, respectively [23]. The lack of effectiveness of influenza vaccination might be 250 attributable to the mismatch in the H3N2 component.…”
Section: Discussionmentioning
confidence: 97%
“…Our estimate was lower than those reported from the United States (61%, 95% CI: 52%, 68%) [19] and Canada (58.5%, 95% CI: 43.9%, 69.3%) [20], which could attribute to different circulating viruses in the two regions. In the 2013- 14 for the elderly aged 65 years or above [20] while a similar study in Spain estimated a 248 moderate influenza VE of 33% (6%, 53%) and 40% (13%, 59%) in all age groups and the elderly, respectively [23]. The lack of effectiveness of influenza vaccination might be 250 attributable to the mismatch in the H3N2 component.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have indicated the benefits of vaccination can extend into the following season [ 5 , 10 , 11 , 12 , 13 , 14 ] while another study indicated that such antibody levels drop below accepted protective levels within a year [ 15 ]. Measurements of HI titers 180 days post-vaccination suggest that a significant portion of vaccinated subjects retain protective titers up to this point [ 16 ], but it is known that a reduction in vaccine effectiveness occurs later in the season, or in between seasons [ 17 , 18 , 19 , 20 ]. This has implications for those travelling between the northern and southern hemispheres, military personal posted to different regions of the globe, and at risk people vaccinated early during a season when influenza virus infections emerge late in the season.…”
Section: Introductionmentioning
confidence: 99%
“…Although the influenza vaccination is widely used nowadays, it remains an important health threat worldwide. The effectiveness of current influenza vaccination is not adequate, and protection rates in elderly people are probably as low as 30% [ 2 , 42 , 43 ]. Multiple factors are responsible for the low protective efficacy; these include antigen drift, seasonal mismatch, and manufacture technique limitations [ 2 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%